Cross-Cultural Language Impoliteness: A Literature Review - Muhammad Yusi Kamhar; Anas Ahmadi; Erma Lestari; Karlina Karadila Yustisia (Program Studi Pendidikan Bahasa dan Sastra Indonesia, 2024)
This literature review study is based on empirical phenomena that show that the phenomenon of language impoliteness across cultures is increasingly worrying. The implications of the phenomenon of language impoliteness often trigger various social problems among cross-cultural communities. Various forms of language impoliteness are often found, including violating the maxims of politeness and engaging in verbal violence, which, of course, can cause fatal problems. This literature review research aims to describe how much previous research in the last three years discussing language impoliteness was searched through electronic databases, namely Google Scholar, Taylor & Francis Online, and ScienceDirect. Meanwhile, the second research aims to find out how much the issue of language impoliteness is of concern to researchers from various circles so that a conclusion can be reached about the urgency of this research topic. This research method is to search various articles published between 2021 and 2023. The search results found 44 articles on the topic of impoliteness, but in the discussion, we will discuss eight articles that are considered the most representative of the 44 articles. These eight articles can represent all the issues that are the topic of discussion of language impoliteness in cross-cultural societies. Thus, it can be concluded that the topic of language impoliteness is still an important issue that requires further study to find various solutions to this problem